2022
DOI: 10.1101/2022.02.24.22270912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic Epigenetic Changes during a Relapse and Recovery Cycle in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome

Abstract: (242) Background Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a complex disease with variable severity throughout the ongoing illness. Patients experience relapses where symptoms increase in severity, leaving them with a marked reduction in quality of life. Previous work has investigated molecular differences between ME/CFS patients and healthy controls, but the dynamic changes specific to each individual patient are unknown. Precision medicine can determine how each patient responds individu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Critically, in mitochondria this can lead to compromised energy production that may have repercussions throughout all body systems and an ability to provide extra energy to manage stress. Our most recent study has followed individual patients through a “relapse/recovery cycle” and has indicated there is a stronger peripheral immune dysfunction and greater inflammatory response during relapse that we infer arises from increased neuroinflammation and, from the altered DNA methylation profiles, changes in the expression of critical genes that would likely mediate this peripheral response in the immune cells ( 49 ). These studies from our group are summarized in the following Sections: Changes in the Transcriptome of Immune Cells in ME/CFS Patients, Differentially Expressed Proteins in the Immune Cells of ME/CFS Patients Analyzed by Sequential Window All Theoretical Spectra Mass Spectrometry MS (SWATH-MS), and A Comparison Between the ME/CFS Patient Cohort and the Healthy Controls Showed Changes in the DNA Methylation Profiles That Reflect Systemic Dysfunctions That Become More Pronounced During a Relapse.…”
Section: Evidence Of An Ongoing Systemic Peripheral Immune/inflammato...mentioning
confidence: 99%
See 2 more Smart Citations
“…Critically, in mitochondria this can lead to compromised energy production that may have repercussions throughout all body systems and an ability to provide extra energy to manage stress. Our most recent study has followed individual patients through a “relapse/recovery cycle” and has indicated there is a stronger peripheral immune dysfunction and greater inflammatory response during relapse that we infer arises from increased neuroinflammation and, from the altered DNA methylation profiles, changes in the expression of critical genes that would likely mediate this peripheral response in the immune cells ( 49 ). These studies from our group are summarized in the following Sections: Changes in the Transcriptome of Immune Cells in ME/CFS Patients, Differentially Expressed Proteins in the Immune Cells of ME/CFS Patients Analyzed by Sequential Window All Theoretical Spectra Mass Spectrometry MS (SWATH-MS), and A Comparison Between the ME/CFS Patient Cohort and the Healthy Controls Showed Changes in the DNA Methylation Profiles That Reflect Systemic Dysfunctions That Become More Pronounced During a Relapse.…”
Section: Evidence Of An Ongoing Systemic Peripheral Immune/inflammato...mentioning
confidence: 99%
“…Datasets generated and analysed for Figure 3 of this study can be found in the GEO database NCBI (GSE166592), see also ( 49 ).…”
Section: Data Availability Statementmentioning
confidence: 99%
See 1 more Smart Citation